APLIKASI TECHNOLOGY ACCEPTANCE MODEL PADA SISTEM INFORMASI MANAJEMEN RUMAH SAKIT - Supriyati Supriyati; Muhammad Cholil (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2017)
The purpose of this study was to apply the Technology Acceptance Model (TAM) in the Management Information Systemof Prof. Dr. R. Soeharso Orthopedics Hospital in Surakarta. This study was an empirical research with quantitative method. The data used comprised of primary and secondary ones. The study population was all employees of Prof. Dr. R. Soeharsowho use the management information system, i.e. 382 people. By using simple random method inthe sampling techniques,193 people were selected as the study sample.The results show that: computer self-efficacy,positively and significantly affects the perception of the benefits and the perceived ease of technology usein the information system of the hospital management; and so subjective norms, itpositively and significantlyaffects the perception of the benefits and the perceived ease of technology use in the hospital management information system; system accessibilitydoes not significantly affect the perception of the benefits, but it gives positive and significant influenceon the perceived ease of technology use in the information system of the hospital management; there isa significant and positive influencefrom the perceived ease of technology use against the perceived benefits of the information system, however, that beneficial perception does not affect the attitude of technology use in the information system of hospital management;the perception of the ease of technology use does not significantly affect the perceived attitude in using the technology, nonetheless, that attitude about the technology use has positive and significant influence against behavioral intention to use the technology in the hospital management information system; and that intention in the technology use, subsequently affects significantly and positively the behavior of the use of the same technology in the hospital management information system ofProf. Dr. R. SoeharsoOrthopedics Hospital of Surakarta. Key words : Technology Accepance Model, Computer Self Efficacy, Subjective Norms, System Accessibility, Perception of Technology Benefits, Attitude of Technology Use, Intention of Technology Use, Behavior of Technology Use,Hospital Management Information System